A Map for the Choice of Landslide Risk Mitigation Countermeasures. (2016) - Bovolenta, Rossella; Berardi, Riccardo; Federici, Bianca; Marzocchi, Roberto
Abstract: The present paper proposes an automatic procedure in GIS providing maps which suggest the more appropriate and feasible intervention type to mitigate landslide risk. These maps are not intended for replacing the designer engineering judgment, nor his work, but to help him in the choice and to help the territorial protection agencies in planning interventions and allocating funds. In order to make available these results to technical staff of public administrations, designers and insurance companies, operating in landslide risk management, the maps referred to Genoa have been published, as an example, on a webGIS site. In the paper, the proposed methodology is described and validation cases are reported.